2015
DOI: 10.4315/0362-028x.jfp-14-273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Micronized Encapsulated Essential Oil–Containing Phosphate and Lactate Blends for Growth Inhibition of Listeria monocytogenes and Salmonella on Poultry Bologna, Pork Ham, and Roast Beef Ready-to-Eat Deli Loaves

Abstract: Essential oils and their constituents are reported to possess potent antimicrobial activity, but their use in food processing is limited because of low solubility in aqueous systems and volatilization during processing. Two proprietary noncommercial essential oil-containing phosphate blends were evaluated for antimicrobial activity against Salmonella enterica cocktail (SC)-and Listeria monocytogenes (Lm)-inoculated deli meat products made from pork, poultry, or beef. Four treatments were tested on restructured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Due in part to their hydrophobicity and volatility, their utility in aqueous foods or in produce washing systems is limited. Nevertheless, encapsulation of EOCs with water-dispersible compounds has been reported by multiple researchers to assist in delivering plant EOCs to microbes in liquid and solid foods (Gaysinsky et al, 2007;Zhang et al, 2008Zhang et al, , 2014Donsì et al, 2011;Gomes et al, 2011;Casco et al, 2015). Our research group recently developed and characterized polymeric nanoparticles formed from the tri-block copolymer Pluronic ® F-127 loaded with the rose oil component geraniol at 0.2 wt.%; geraniolloaded polymeric nanoparticles (GPNs) were inhibitory to E. coli O157:H7 and Salmonella growth in liquid medium incubated at 35°C.…”
mentioning
confidence: 99%
“…Due in part to their hydrophobicity and volatility, their utility in aqueous foods or in produce washing systems is limited. Nevertheless, encapsulation of EOCs with water-dispersible compounds has been reported by multiple researchers to assist in delivering plant EOCs to microbes in liquid and solid foods (Gaysinsky et al, 2007;Zhang et al, 2008Zhang et al, , 2014Donsì et al, 2011;Gomes et al, 2011;Casco et al, 2015). Our research group recently developed and characterized polymeric nanoparticles formed from the tri-block copolymer Pluronic ® F-127 loaded with the rose oil component geraniol at 0.2 wt.%; geraniolloaded polymeric nanoparticles (GPNs) were inhibitory to E. coli O157:H7 and Salmonella growth in liquid medium incubated at 35°C.…”
mentioning
confidence: 99%
“…In addition, it was reported that 2% potassium lactate could ensure microbial quality of roast beef towards the proliferation of L. monocytogenes and inoculated Salmonella cocktail composed by Salmonella typhimurium, Salmonella Heidelberg, and Salmonella Enteritidis [64].…”
Section: Beef Meatmentioning
confidence: 99%
“…Added to that, it was demonstrated that potassium lactate at 2% inhibited the growth of L. monocytogenes and Salmonella spp. in cured pork meats for 49 days of refrigerated storage [64].…”
Section: Pork Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization (WHO), one of the most serious foodborne diseases is caused by Listeria monocytogenes (WHO, 2018a) while one of the four most important global causes of diarrheal diseases is attributed to Salmonella (WHO, 2018b). Since ready‐to‐eat (RTE) protein‐based products like cold cuts and deli meats may be consumed without an additional cooking or heating step, they have been implicated in the risk of foodborne diseases caused by the ingestion of the mentioned pathogenic bacteria (Casco, Taylor & Alvarado, 2015; Ricci et al, 2018). On a risk assessment study supervised by the Food Safety and Inspection Service (FSIS) of the United States Department of Agriculture (USDA), it was predicted that around 70% of the cases of disease and death from L. monocytogenes would be caused by the ingestion of the bacteria through RTE meat and poultry deli meats with no added antimicrobial growth inhibitors and which are sliced at retail points (Quesenberry et al, 2010); in the same study, the importance of the use of microbial growth inhibitors in these products became evident when comparing the estimated percentage of deaths from L. monocytogenes ingestion through retail‐sliced deli meats without growth inhibitors (73.2%) and retail‐sliced deli meats with growth inhibitors (16.9%).…”
Section: Introductionmentioning
confidence: 99%